Непрямий умисел при вчиненні насильства щодо працівника правоохоронного органу - Бойко, Андрій Володимирович; Бойко, Андрей Владимирович; Bojko, Andrej (Одеса : Юрид. л-ра, 2012)
Article is devoted research of problеms of the signs of t h e subjective part y of violence connected with definition concerning the worker of the law enforcement body provided by article 345 of the Criminal Code of Ukraine .
Бойко А. В. Непрямий умисел при вчиненні насильства щодо працівника правоохоронного органу / А. В. Бойко // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 631-637.
Keywords: кримінальне право; насильство щодо працівника правоохоронного органу; непрямий умисел; уголовное право; насилие относительно работника правоохранительног о органа; criminal law; violence concerning t h e worker of law enforcement body; indirect intention